Differentiation of Bartonella Species by a Microimmunofluorescence Assay, Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis, and Western Immunoblotting - Liang, Zhongxing (American Society for Microbiology, 2000)
Bartonella species can be differentiated by microimmunofluorescence assay, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and immunoblotting with murine polyclonal antisera to Bartonella henselae, B. quintana, B. elizabethae, and B. bacilliformis. A pairwise comparison on the basis of SDS-PAGE protein profiles demonstrated similarity values for proteins of different Bartonella species ranging from 28.6 to 86.4%. Antigenic relationships revealed by immunoblotting with murine antisera were equivalent to those of proteins observed by SDS-PAGE. A dendrogram obtained on the basis of protein bands of SDS-polyacrylamide gels showed that Bartonella species could be divided into three groups. B. bacilliformis was distinct from all other Bartonella species; B. grahamii, B. taylorii, B. doshiae, and B. vinsonii formed a cluster, as did B. henselae, B. quintana, B. elizabethae, and B. clarridgeiae. These relationships were consistent with those revealed by parsimony trees derived from 16S rRNA and gltA gene sequencing. SDS-PAGE analysis showed that 120-, 104-, 85-, 71-, 54-, 47-, 40-, 33-, 30-, and 19-kDa proteins were present in all species, with the 54-kDa protein being the most dominant. Proteins with a molecular mass of less than 54 kDa allow the differentiation of species and are a possible target for future species-specific antibodies and antigens.